Study of the Utilization of Venues for the XXth National Sports Week After the Implementation in Nolokla Village, East Sentani District, Jayapura Regency - Ohee, Glen Malimongan; Simbiak, Irja Tobawan; Sudiro, Sudiro; Ramandei, Lazarus (Yayasan Banu Haji Samsudin, 2025)
The National Sports Week (PON) venue is used as a place for sports and to hold various matches. However, post-implementation of PON in Papua Province, there were many concerns that the venues built were not being used and utilised optimally according to their intended use. Apart from that, the high cost of maintaining venues for PON located in Papua Province was an obstacle for the government. The research applied a mixed qualitative and quantitative approach which was the answer to the research questions. The results of the research found data related to the use and physical condition of the PON venue which had been recapitulated by data from a note on the assessment index by each PON venue. Furthermore, Interview transcripts were also used as supporting data for research which discusses future strategies by the Sports and Youth Department in managing each PON venue so that they would be utilized continuously. Moreover, the researcher received input in the form of funds that focus on venue maintenance costs so that in the future it would be utilized consistently by many people and athletes who compete to carry the name of Papua Province in the sports sector. Next, it could also be developed into sports-based tourism to introduce sports equipment to the public and facilitate equipment in sports competition activities. Keywords: PON venue, sports facilities, sports